Desafios da implementação da política pública de arquivos: as funções arquivísticas e o acesso à informação na Prefeitura Municipal de Vitória, ES. - Luiz Carlos da Silva (2020)
The thesis was initially based on the hypothesis that the effective implementation of archival functions (production, classification, evaluation, acquisition, conservation, description, diffusion) would be the basis for enabling the public policy of access to information. But this research it was found that these principles were not observed. Therefore, that hypothesis was reformulated and we sought to show that even in environments where there is no archive policy - the basis for a secure retrieval of recorded information - the Law on Access to Information is being implemented by the Municipal Comptroller General to assist the Citizen Information System.The research is linked to other theoretical concerns regarding the interdisciplinarity between Archival and Information Sciences. Regarding methodological issues, the diagnosis of the Greater Vitória Metropolitan Region was initially developed to delimit the field of study. The criteria adopted showed that the City Hall of Vitória presented a better structure in relation to the archival functions and for this reason the archival policies implemented by the Vitória General Archive were analyzed. However, such policies have been found to be deficient, but amenable to solution, but if neglected can compromise the informational process. Regarding the information access, after surveys with the Controllership General of the Municipality it was found that the documents are rarely used to answer the E-Sic, which can lead to the risk of legal uncertainty because the information alone does not proceed. On the other hand, a manageable, evidential, and stable archive document guarantees the value of the proof. It is a qualitative research about the method or approach, descriptive about the objectives and a case study about the research procedure. The general objective is to present a study of archival public policy through archival functions, in order to identify the complications that interfere with the retrieval of information in the Archive of the Vitória City Hall. The specific objectives are: to establish a dialogue on the interdisciplinarity between Archival and Information Science; to present a study on information and archival policy; to develop reconsiderations about the concepts of archives, public archives and municipal archives; to analyze of archival functions; to demonstrate the policy of access to information in the City Hall of Vitória through the Comptroller General of the Municipality; and to propose solutions as a contribution of research to improve the current conditions in which the General Archive of Vitória is presented. This these concludes the urgency of both managerial and punctual actions, which are essential for the good management of public resources and the effective exercise of democracy at the municipal level, because the deficit of archival policies is above all a deficit of citizenship. Macro-problems and micro-problems should be the target of immediate action to avoid compromising the quality of municipal management, and consolidate the guarantee of preservation of archival documentary heritage.